Taking the Participatory Integrated Climate Services for Agriculture (PICSA) approach to extension actors for strengthening resilience in Africa: five years’ experience in West Africa - Ky-Dembélé, Catherine; Bayala, Jules; Dayamba, Djibril S; Adeyemi, Chabi; Dorward, Peter; Agali, Alhassane; Diakité, Adama; Zougmoré, Robert B.; Lamien, Niéyidouba (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
In West Africa, about 70% of the population live in rural area and have livelihoods mostly based on rainfed agriculture (Connolly-Boutin and Smit 2016; Serdeczny et al. 2017). Despite the low input practices, agriculture contributes of 30-40% Gross Domestic Product (Jalloh et al. 2012; Nin-Prat et al. 2011). However, farmers in this region are exposed to various weather-related risks, chiefly climate variability as well as climate change inducing droughts, which combined with their low adaptive capacities makes them the most vulnerable in the world (Von Soest 2020). Moreover, the climate of West Africa is expected to become more arid due to increased temperature and uncertain rainfall regimes, while its population is expected to grow faster than the rest of the world (Mechiche-Alami and Abdi 2020). Climate smart agriculture aims at helping farmers cope with the negative impact of climate change and in line with this, accurate and timely climate information services are one of the major inputs for improving agricultural practices (FAO 2013, 2018; Hansen et al., 2011, 2019). Developed by the University of Reading, within the framework of a CCAFS (Climate Change Agriculture and Food Security research program) funded project and with initial support from Nuffield Africa, the Participatory Integrated Climate Services for Agriculture (PICSA) approach is designed to help mallholder farmers to make plans and decisions for their individual contexts and that utilize climate and weather information together with participatory decision making tools. This approach is based on the analysis of livelihood activities by smallholder farmers in the light of climate information of their locality including historical weather data as well as seasonal and short-term forecasts, and helps farmers to make risk assessments and decisions to improve their production and meet their objectives (Dorward et al. 2015). Various participatory tools, including resource allocation maps, seasonal calendars, participatory budget analysis, C C A F S I N F O N O T E 2 are used for such analysis considering the specific context of each farmer as shown in the contextual framework in Figure 1. Two key principles of PICSA include ‘the farmer decides’ i.e. that farmers are best placed to make decisions about their agricultural practices, because they have detailed knowledge of their farm, system and environment, and they also face the consequences (whether favourable or unfavourable) of their decisions, and ‘options by context’ i.e. different farmers having different contexts. This includes differences in wealth, education, land, goals and attitudes to risk. Therefore, what works for one farmer might not work for another and farmers should thus make decisions that are right for their own contexts (see https://research.reading.ac.uk/picsa for full explanation and resources on PICSA).